ANALISIS KONSEP TAQWA DALAM AL-QURAN: Studi Terhadap Ayat-Ayat yang Menyebutkan Taqwa - Fadillah, Ivan Fahmi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Taqwa is a central concept in Islam that describes a person's awareness, obedience, and piety to Allah. This concept is consistently mentioned in the Quran, providing guidance for Muslims to develop a deeper relationship with God and achieve spiritual success in life. Although piety is the center of attention in Islam, in-depth analysis of this concept in the Qur'an is still limited. Therefore, this research aims to study the concept of piety in the Quran and analyze the verses that contain it. This research uses the method of analyzing the Al-Quran text with a qualitative approach. The data is obtained from the verses of the Quran that specifically contain the word